Survey on AIAOD: Advanced Intelligent Abandoned Object Detection - Hargude, Sonali A; Idate, SR (International Journal of Computer Sciences and Engineering, 2025)
Object detection and tracking is a very challenging task in image processing. This paper discusses about various object detection and tracking methods for crowded area such as airports, railway stations, shopping malls, residential apartment . Three major steps in video surveillance analysis are detection of moving objects, track those objects from frame to frame and recognise behaviours of those track objects to find out for suspicious activity detection. This paper mainly highlights the various object detection, object representation and object tracking techniques which are performed by different researchers in the past. This survey focused on different object detection using - background subtraction, fuzzy logic, temporal logic, hadoop, via temporal consistency modelling, nonflat static objects detection, abandoned detection of object in real time environments, detection of object on the basis of 3-dimensional image information. The usage of object tracking is for public safety, for efficient traffic management on roads , to fight against crime and terrorism.